Enhancing the in Vitro Response of explants from mature Jack (Artocarpus heterophyllus Lam.) Trees - Reena Philip (Department Of Horticulture, College Of Agriculture, 1993)
The objective of the present study was to improve the propagation efficiency of mature phase jack trees by various pretreatments. The treatments tried involved stock plant treatments, explants treatments and in vitro treatments. Surface sterilization with HgCl2 for 13 minutes was found to be the most effective in reducing microbial contamination during culture establishment. Among the stock plant treatments tried, grafting on to juvenile rootstock was found to be the most effective in improving the in vitro response of explants from mature jack trees. Stress treatments were found to be the most effective among the explants treatments. Cold shock for 5 minutes at – 200C was found to produce the best results followed by heat treatment at 420 C for 2 minutes. Among the in vitro treatments, incorporation of phloroglucinol at the rate of 10mg/l was found to be the most effective. The results also showed significant influence of season on the response of mature explants, the highest response being observed during March – April.